Relationships between physical characteristics and ranking of young tennis players - Meckel, Y.; Hophy, A.; Dunsky, A.; Eliakim, A. (Central European Journal of Sport Sciences and Medicine, 2015)
The purpose of the present study was: 1) to determine young tennis players` fitness and anthropometric characteristics; and 2) to determine to what extent these characteristics relate to the players` national ranking. Forty young (age 15.1 ±0.4) trained male tennis players, who were ranked from 1 to 40 in their age group in the country`s youth tennis players list, were tested for speed, speed endurance, flexibility, strength, specific agility and quickness, aerobic capacity, height, and weight. Significant correlations were found between the players` ranking and speed (r = 0.430 - 0.475), specific agility and quickness (r = 0.626), speed endurance (r = 0.562), strength (r = -0.416), aerobic capacity (r = -0.581), flexibility (r = 0.352), height (r = -0.443), and weight (r = -0.293). Stepwise regression analysis indicated that specific agility and quickness accounted for almost 40% of the players` ranking, while its combination with the players` height accounted for 56%. The results imply the overall importance of anaerobic capabilities and tennis-specific movements to the young tennis players` ranking. The results also emphasize the importance of tennis-specific tests to the young tennis players` performance evaluation.